2020
DOI: 10.1007/s10096-020-03948-y
|View full text |Cite
|
Sign up to set email alerts
|

Virulence of Helicobacter pylori outer membrane proteins: an updated review

Abstract: Helicobacter pylori (H. pylori) infection is associated with some gastric diseases, such as gastritis, peptic ulcer, and gastric cancer. CagA and VacA are known virulence factors of H. pylori, which play a vital role in severe clinical outcomes. Additionally, the expression of outer membrane proteins (OMPs) helps H. pylori attach to gastric epithelial cells at the primary stage and increases the virulence of H. pylori. In this review, we have summarized the paralogs of H. pylori OMPs, their genomic loci, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 103 publications
1
55
0
1
Order By: Relevance
“…H. pylori infection usually occurs in childhood, and when untreated, remains present in the life of the host [ 3 , 6 , 11 ]. The infection is usually associated with asymptomatic gastritis, and in the long-term it may result in more severe clinical outcomes, such as gastric ulcer, duodenal ulcer, and gastric cancer [ 2 , 3 , 4 , 12 , 13 ]. This bacterium has various virulence factors, including a cytotoxin-associated gene A (CagA), a vacuolating cytotoxin A (VacA), and various outer membrane proteins that allow this microorganism to move around and survive in the unfavorable environment of the human stomach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…H. pylori infection usually occurs in childhood, and when untreated, remains present in the life of the host [ 3 , 6 , 11 ]. The infection is usually associated with asymptomatic gastritis, and in the long-term it may result in more severe clinical outcomes, such as gastric ulcer, duodenal ulcer, and gastric cancer [ 2 , 3 , 4 , 12 , 13 ]. This bacterium has various virulence factors, including a cytotoxin-associated gene A (CagA), a vacuolating cytotoxin A (VacA), and various outer membrane proteins that allow this microorganism to move around and survive in the unfavorable environment of the human stomach.…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium has various virulence factors, including a cytotoxin-associated gene A (CagA), a vacuolating cytotoxin A (VacA), and various outer membrane proteins that allow this microorganism to move around and survive in the unfavorable environment of the human stomach. Moreover, CagA and VacA may deregulate the host’s intracellular signaling pathways, promoting neoplastic transformation [ 2 , 13 , 14 ]. CagA can interact with the host’s proteins to activate further signaling pathways, thereby activating the host’s inflammatory responses and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…While a subpopulation of H. pylori is free-swimming in the mucus, some bacteria are able to attach to and colonize the intercellular junctions of epithelial cells. Several molecular adhesins, such as BabA, SabA and HopQ, have been described to be important for the attachment to epithelial cells [ 112 ]. Salama and colleagues found that the helical shape of H. pylori allows the bacterium not only to swim directedly in the mucus but also to interact with the host and induce inflammation [ 113 ].…”
Section: The Model Pathogen: Helicobacter Pylorimentioning
confidence: 99%
“…Strains that produce multiple virulence factors are believed to have a greater potential to persistently infect the stomach [ 19 ]. The classically mentioned virulence determinants include urease [ 20 ], vacuolating toxin (VacA) [ 21 ], cytotoxic oncoprotein (CagA) [ 22 ], and numerous adhesins [ 23 ]. However, more and more often attention is paid to the morphological transformation of this bacterium as one of the key properties conditioning the survival of H. pylori [ 24 ].…”
Section: Introductionmentioning
confidence: 99%